Self-Regulated Writing (SRW) strategies during the completion of dissertation: a case study - M. Affandi Arianto; Anik Nunuk Wulyani (Jurnal Cakrawala Pendidikan, 2022)
Previous studieshave highlighted the benefits of self-regulated writing (SRW) strategies in the EFL/ESL context. However, little is known about the use of these strategies inthe process of completing a dissertation. Anchored by the limitations of previous studies, this case study aimed to investigate and understand the use of SRW strategies by Indonesian doctoral students majoring in English Language Education. Through purposive sampling, four doctoral students at a public university in Indonesiawere selected as the participants. The data were collected through semi-structured interviews. The qualitative data analysis indicated that the participants used eight SRW strategies, namely idea planning, noticing, text processing, selecting physical environments, seeking social assistance, feedback handling, goal-oriented monitoring and evaluating, and self-talk. This article provided descriptions and explanations of how each strategy was used in the process of completing the participants’ dissertations. The findings of this study also provide pedagogical implications especially in raising doctoral students’ awareness in using SRW strategies as well as contributing to the theoretical development of SRW theory.